NIETZSCHE, FREUD AND THE SOCIOLOGY OF RISK. REFLEXIVITY, BODY AND UNCONSCIOUS - Drivet, Leandro (2013)
This paper attempts to point out the implicit relevance of some specific categories of Nietzschean and Freudian thoughts on contemporary developments in the Sociology of Risk, with the dual purpose of (i) make a small contribution to the understanding of the subject area and (ii) demonstrate the relevance of the works of Nietzsche and Freud for self-understanding of our cultural experience as members of modern societies in the historical context of late capitalism.